Resveratrol 3‐O‐d‐glucuronide and resveratrol 4′‐O‐d‐glucuronide inhibit colon cancer cell growth: Evidence for a role of A3 adenosine receptors, cyclin D1 depletion, and G1 cell cycle arrest. Issue 10 (7th May 2013) - Polycarpou, Elena; Meira, Lisiane B.; Carrington, Simon; Tyrrell, Elizabeth; Modjtahedi, Helmout; Carew, Mark A.
<x xml:space="preserve">Abstract</x> Scope Resveratrol is a plant‐derived polyphenol with chemotherapeutic properties in animal cancer models and many biochemical effects in vitro. Its bioavailability is low and raises the possibility that the metabolites of resveratrol have biological effects. Here we investigate the actions of resveratrol 3‐O‐d‐glucuronide, resveratrol 4′‐O‐d‐glucuronide, and resveratrol 3‐O‐d‐sulfate on the growth of colon cancer cells in vitro. Methods and results The growth of Caco‐2, HCT‐116, and CCL‐228 cells was measured using the neutral red and MTT assays. Resveratrol and each metabolite inhibited cell growth with IC50 values of 9.8–31 μM. Resveratrol caused S phase arrest in all three cell lines. Resveratrol 3‐O‐d‐glucuronide and resveratrol 4′‐O‐d‐glucuronide caused G1 arrest in CCL‐228 and Caco‐2 cells. Resveratrol 3‐O‐d‐sulfate had no effect on cell cycle. Growth inhibition was reversed by an inhibitor of AMP‐activated protein kinase (compound C) or an adenosine A3 receptor antagonist (MRS1191). The A3 receptor agonist 2Cl‐IB‐MECA inhibited growth and A3 receptors were detected in all cell lines. The resveratrol glucuronides also reduced cyclin D1 levels but at higher concentrations than in growth experiments and generally did not increase phosphorylated AMP‐activated protein kinase. Conclusion Resveratrol glucuronides inhibit cell growth by G1 arrest and cyclin D1 depletion, and our results strongly suggest a role for A3 adenosine receptors in this inhibition.